2018
DOI: 10.1155/2018/6597387
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin as a Prognostic Marker in Acute Chest Pain and Suspected Acute Coronary Syndrome

Abstract: Background In patients admitted with chest pain and suspected acute coronary syndrome (ACS), it is crucial to early identify those who are at higher risk of adverse events. The study aim was to assess the predictive value of copeptin in patients admitted to the emergency department with chest pain and nonconclusive ECG. Methods Consecutive patients suspected for an ACS were enrolled prospectively. Copeptin and high-sensitive troponin T (hs-TnT) were measured at admission. Patients were followed up at six and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In contrast to cTn, the release of copeptin is unspecific and may be stimulated by numerous acute clinical pathologies, including acute heart failure, pulmonary embolism, and sepsis [10][11][12][13]. Previously, elevated copeptin values in patients with suspected ACS but also non-ACS conditions were found to confer incremental prognostic information beyond an increased hs-cTn [10,14]. However, Stallone et al found that the association of elevated copeptin levels with mortality may be largel, y explained by age and comorbidities [9].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to cTn, the release of copeptin is unspecific and may be stimulated by numerous acute clinical pathologies, including acute heart failure, pulmonary embolism, and sepsis [10][11][12][13]. Previously, elevated copeptin values in patients with suspected ACS but also non-ACS conditions were found to confer incremental prognostic information beyond an increased hs-cTn [10,14]. However, Stallone et al found that the association of elevated copeptin levels with mortality may be largel, y explained by age and comorbidities [9].…”
Section: Introductionmentioning
confidence: 99%
“…10,24,25) In a study, Morawiec et al found that 17.4 pmol/L was a significant copeptin value for NSTEMI patients. 26) In another study, Reinstadler et al found that the threshold for the copeptin level was 16.7 pmol/L to predict the left ventricle's performance and adverse remodeling in STEMI patients. 22) In our study, the threshold value of 18.3 pmol/L, which was chosen to predict a high SYNTAX score, is consistent with that in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of the probability of the development of adverse events in the short term after admission is crucial in regard to triage, diagnostic, and therapeutic decisions. Biomarker-based algorithms have a well-established role in this setting [ 1 , 8 , 14 , 22 ]; however, high safety is achieved with serial sampling. Considering the constant need to shorten the time to diagnosis, several clinical scores, e.g., the modified HEART score, are under debate.…”
Section: Discussionmentioning
confidence: 99%
“…Even though lower than hs-TnT/mHS/copeptin, the hs-TnT/mHS algorithm still remains of better sensitivity/NPV than hs-TnT alone, thus reinforcing the interest for the mHS. Copeptin has an advantage over hs-TnT for long-term risk stratification [ 22 ] but has not been analysed neither with mHS nor hs-Tn for short-term risk. Combination of hs-TnT, copeptin, and the mHS, which represent different pathophysiological axes and carry complementary information on the origin and the character of chest pain and possible myocardial ischemia, results in an algorithm of excellent prognostic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation